2023
DOI: 10.1063/5.0119375
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort channel chemical vapor deposited bilayer WS2 field-effect transistors

Abstract: Two-dimensional transition metal dichalcogenides (TMDs) are potential candidates for next generation channel materials owing to their atomically thin structure and high carrier mobility, which allow for the ultimate scaling of nanoelectronics. However, TMDs-based field-effect transistors are still far from delivering the expected performance, which is mainly attributed to their high contact resistance and low saturation velocity ( vsat). In this work, we report high-performance short-channel WS2 transistors ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the FET domain, the key performance indicators for recently described FETs using 2D materials are collated and benchmarked in Table 1 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Graphene shows a very high field-effect mobility (μFE) of 30,000 cm 2 /Vs, as seen in real device simulations, which far exceeds other materials.…”
Section: Graphene Field-effect Transistorsmentioning
confidence: 99%
“…In the FET domain, the key performance indicators for recently described FETs using 2D materials are collated and benchmarked in Table 1 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Graphene shows a very high field-effect mobility (μFE) of 30,000 cm 2 /Vs, as seen in real device simulations, which far exceeds other materials.…”
Section: Graphene Field-effect Transistorsmentioning
confidence: 99%
“…Notably, recent advancements in ultrashort channel CVD 1L-WS 2 MOSFETs have shown an on-current of 320 μA/μm ( L DS = 30 nm) with Ni contacts . The pinnacle of performance in CVD 2L-WS 2 devices was achieved by Shi et al, who reported an on-current of 635 μA/μm at V DS = 1 V, with an ultrashort channel length of 18 nm and Ni contacts (Table S2). Meanwhile, Lin et al demonstrated an on-current of 310 μA/μm for a CVD 2L-WS 2 device with an L DS of 100 nm .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, vapor-phase epitaxy stands out as an effective method for creating high-quality van der Waals contacts. Transport simulations have revealed that bilayer (2L) TMDCs outperform their monolayer (1L) counterparts due to their enhanced intrinsic mobility and density of states. , Furthermore, the durability of 2L materials against fabrication-induced damage helps mitigate extrinsic disorder-induced gap states, thereby alleviating FLP and reducing the SBH at the M–S interface. Among TMDCs, WS 2 has attracted increasing research interest for its application in MOSFETs owing to its large band gap, high mobility, high saturation velocity, and its potential for symmetric n-type and p-type FET performance. , …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, 2D materials can retain their intrinsic electrical properties without compromising mobility, even at the ultimate scaling limit, due to their atomically thin nature. , The high-field transport properties and current saturation behavior of van der Waals (vdW) semiconductors have been rigorously studied for application to next-generation communication systems. Graphene shows a high υ sat of up to 6 × 10 7 cm/s at room temperature (RT) and is a promising candidate for ultrahigh radio frequency (RF) transistors, but the zero band gap nature of graphene causes high off-current, limiting its application in integrated circuit technology. , 2D transition metal dichalcogenides (TMDCs), such as molybdenum disulfide (MoS 2 ) and tungsten disulfide (WS 2 ), show relatively low υ sat values of 3–6 × 10 6 and 3.8 × 10 6 cm/s, respectively, at RT, due to the high impurity scattering rates and corresponding low mobilities (generally <100 cm 2 /(V s)). …”
Section: Introductionmentioning
confidence: 99%